Limites constitucionais às punições indígenas Kaigang - Siviero, Filipe Andrios Brasil (2023)
This research arises from the need to find a solution to the problems daytime events that occur with the Kaingang indigenous communities in the north of Rio Grande do Sul. Indigenous people are constitutionally guaranteed their cultural rights: social organization, customs, languages, beliefs and traditions. However, on a daily basis, individual rights and guarantees indigenous people are violated, within indigenous lands, by leaders, without any refuge State. Quite the contrary, with conscious omission or even stimulation, of the organs that should be responsible for defending the individual rights and guarantees of indigenous people within of their lands. At this point, the importance of studying the applicability of fundamental rights in indigenous private relations, in order to make the maintenance of indigenous ways of life compatible specific rights that respect the fundamental rights of indigenous people. From a reflection historical and anthropological view of the Kaingang legal worldview, there are violations of rights fundamental rights of those within the community, without the possibility of defense in the face of power of leadership. The kaingang worldview, according to anthropology, has always been permissive adaptation to the exogenous factors of the community, from the relationship between the Kaingang and te Jesuits, passing through the relationship between the chiefs and the provincial governments of the Empire for the protection of territories, and finally, in the Republic through the assimilation of methods of punishment and social organization, along military lines. Symbiosis with exogenous factors appears, to a high degree, in the north of Rio Grande do Sul, during the expansionism of the leasing of indigenous lands for the soybean plantation. Kaingang factionalism erupts in several conflicts over the chiefdom, which implies the power to manage land, accumulate money and apply penalties within indigenous prisons. Once the clash of cultures has been verified, it is necessary to find compatibility between legality kaingang and respect for the fundamental rights of these less favored indigenous people, first through cultural dialogue and if this is not possible through the prevalence of fundamental rights individual. This is because cultural rights have constitutional limits entrenched by individual fundamental rights, for formal and material reasons. Formally, when respects the constitutional text and fundamental and material rules, as they are more close to the core content of human dignity. Therefore, self-determination of peoples enshrined by multiculturalism must coexist with fundamental rights, establishing objective parameters for cases of abuse of cultural rights and the autonomy of kaingang customary law and thus be persecuted and held responsible by the institutions of the State, otherwise the duty to protect fundamental rights is violated.